Revitalisasi Usul Fiqh dalam Menghadapi Perubahan Sosial - Abdul Basith Junaidy (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2009)
Historically speaking, the science of usul al-fiqh has not been able to play its role in providing solutions for the many social problems facing human kind. The reason for this lies in that this science does not have within its reservoir the theoretical tools relevant for the renewed human situations. One of the mistakes of this science furthermore is that it produces the jurists who are incapable of adapting to new circumstances. The paradigmatic mode of this science is such that one upon using its premises and methodscannot be analytical and would remain literal. In the other words, this science is very much bayani as opposed to burhani, that is rational and systematic, or irfani which is intuitive. The static nature of usul al-fiqh in the meantime has provoked many jurists to revolt against it and tried to bring about new methods and modes of thinking within it. Thus, we have at least two modes of thinking currently available as far as renewal of u??l al-fiqh is concerned. The first is what we may call utilitarian and the second is liberal. The former bases its theories and ideas on the notion of maslaha. This school of thought is mainly propagated by al-Shatibi. It claims that the whole purpose of Shar??ah is none other than for the good of human being. This general proposition underlies the whole theories that the proponents of this mazhab articulated. The second mode of thought, the liberal, claims that the traditional jurisprudence must be totally replaced by the new one. And to do this the liberals appropriates the hermeneutical approach to interpret the Islamic law according which the intrinsic relationship between the text and its context cannot be revealed through the literal understanding of the message of Islam. The literal approach has thus far failed and is unable to face the new circumstances. This mode of thinking is committed to what its proponents call the real Islamic values inherent within the text of religion. Nasr Hamid Abu Zaid is the staunchest propagator of this current of thought. He proposes new method for usul al-fiqh by criticizing both the classical and contemporary discourses using semiotics as the tools of analysis. In this way, he hopes that more humanist and adapting science of fiqh, one that can respond to our formidable contemporary challenges, may emerge.